E-061 Safety and efficacy of the pipeline embolization device for treatment of ruptured intracranial aneurysms. (23rd July 2017) - Almandoz, J Delgado; Kayan, Y; Uittenbogaard, K; Scholz, J; Milner, A; Fease, J; Wallace, A; Nelson, K; Mulder, M
Abstract : Purpose: To examine clinical and angiographic outcomes in a cohort of consecutive patients with ruptured intracranial aneurysms treated with the Pipeline Embolization Device (PED) at a referral center. Methods: We conducted a retrospective review of all patients with ruptured intracranial aneurysms treated with the PED in our center between January 20 th, 2012 and March 9 th, 2017. Baseline patient and aneurysm characteristics as well as complications were recorded. Aneurysm volumes in initial and follow-up angiographic studies were calculated using AngioCalc. Clinical outcomes were categorized using the modified Rankin Scale (mRS). Results: 16 patients underwent 17 PED procedures to treat 18 ruptured intracranial aneurysms during the study period. 11 patients were women (69%) and 5 men (31%). Mean age was 53 years (range 13-92 years). Hemorrhage distribution was diffuse in 12 patients (75%), perimesencephalic in 2 patients (13%), peripheral in 1 patient (6%) and intraventricular in 1 patient (6%). Mean admission Hunt-Hess scale was 2.4 (median 2, range 1-5). 5 patients required external ventricular drain (EVD) placement (31%). 13 patients were premedicated with aspirin/clopidogrel with VerifyNow testing (81%), 1 with warfarin/clopidogrel with VerifyNow testing (6%) and 2 with aspirin/ticagrelor without VerifyNow testing (13%). 11 aneurysms were treated acutely (61%, mean 3.1 days after hemorrhage, range 0-7 days), and 7 subacutely (39%, mean 31 days after hemorrhage, range 8–76 days). 9 aneurysms were blister (50%), 5 saccular (28%), 3 dissecting (17%) and 1 fusiform (6%). 11 aneurysms were located in the internal carotid artery (61%), 3 in the basilar artery (17%), 2 in the middle cerebral artery (11%) and 2 in the anterior cerebral artery (11%). Mean aneurysm size was 3.3mm (1.5–10.8mm), mean neck was 2.8mm (0.6-8.3mm), mean dome-to-neck ratio was 1.1 (0.7–2.8). Mean number of PEDs deployed per aneurysm was 1.1. Adjunctive coiling was performed in 3 aneurysms (17%, mean 2.3 coils deployed). There were 1 intra-operative (6%) and 2 peri-operative (12%) complications, none led to a disabling neurological deficit (mRS≥3). There were 2 post-operative aneurysm re-ruptures (11%), 1 occurring on post-operative day 1 without clinical sequelae, and 1 occurring on post-operative day 14 upon EVD removal and resulting in the patient's death. Both aneurysms with post-operative re-rupture were dissecting anterior cerebral artery aneurysms treated acutely without adjunctive coiling. Treatment-related mortality was 6.3%, and overall mortality was 12.5%. Angiographic follow-up was available in 8 aneurysms (44%, 6 follow-ups currently pending), with a mean time to last angiographic follow-up of 12.4 months. At last follow-up, 7 aneurysms were completely occluded (88%) and 1 aneurysm had near-complete occlusion (12%, 92.9% volume reduction). The nearly-completely-occluded aneurysm was re-treated with placement of an additional PED. At last clinical follow-up, 11 patients had mRS 0–2 (68.8%), 3 had mRS 3 (18.8%) and 2 had expired (12.5%). Conclusion: The PED is a safe and effective treatment for ruptured intracranial aneurysms, with high medium-term complete aneurysm occlusion rates, low re-treatment rates, and a low rate of major treatment-related complications. The risk of post-operative aneurysm re-rupture may be minimized by adjunctive use of coils and subacute PED embolization whenever possible. Disclosures: J. Delgado Almandoz: 2; C; Medtronic Neurovascular, Accriva Diagnostics. Y. Kayan: 2; C; Medtronic Neurovascular. K. Uittenbogaard: None. J. Scholz: None. A. Milner: None. J. Fease: None. A. Wallace: None. K. Nelson: None. M. Mulder: None.